Non-Hodgkin Lymphoma Prognostic Factors and Targets - Quesenberry, Peter J.; Castillo, Jorge J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Recent developments in the therapy of non-Hodgkin lymphoma have improved response and survival rates in patients with these conditions. This book is focused on the biology, prognostic factors and novel targets of non-Hodgkin lymphoma. We believe that understanding the pathophysiology of non-Hodgkin lymphoma provides a mean to improve its risk-stratification and treatment. This book is intended for medical and healthcare professionals involved in the research and clinical care of patients with non-Hodgkin lymphoma.
Cancer Stem Cells: A Matter of Perspective -- B and T-cell development -- HIV lymphomagenesis -- Epstein-Barr Virus Lymphomagenesis and Therapeutic Targets -- Antigen driven lymphomagenesis -- Pre-clinical lymphoma models -- Prognostic factors in B-cell lymphoma -- Prognostic factors in T-cell lymphoma -- Prognostic factors in HIV-associated lymphoma -- Future directions on the treatment of aggressive non-Hodgkin lymphoma -- New monoclonal antibodies for indolent non-Hodgkin lymphomas -- Current therapies for T-cell lymphoma -- Stem Cell Transplantation for lymphoma -- Autologous stem cell transplantation in non-Hodgkin lymphoma -- The role of Stem Cell Transplantation for HIV-associated lymphoma -- Stem Cell Transplantation for T-cell lymphoma -- Index.
Keywords: Medicine; Cancer research; Pharmacology; Biomedicine; Cancer Research; Pharmacology/Toxicology.; Electronic books